Dissolution–Crystallization Transition within a Polymer Hydrogel for a Processable Ultratough Electrolyte. Issue 30 (11th June 2019) - Wei, Junjie; Wei, Gumi; Shang, Yinghui; Zhou, Jie; Wu, Chu; Wang, Qigang
Abstract: Although nonliquid electrolytes have been developed rapidly under the condition of safe demand of energy storage devices, the inherent weaknesses in ionic conductivity, mechanical properties, or interfacial compatibility severely hinder their application under a harsh environment. Inspired by the hybridized characteristics of composite materials and the potential advantages of hydrated crystals, a processable crystal‐type gel electrolyte with good comprehensive performance via the dissolution–crystallization transition of NaAc within hydrogel is creatively prepared. The use of NaAc crystal within a hydrogel leads to nearly 26 000 times greater modulus (474.24 MPa) and higher operating voltage (2.0 V) than the hydrogel without the crystal. The reliable supercapacitor using this electrolyte can work in extreme environment (−40 to 80 °C, even in the fire or in liquid nitrogen within a short time) benefiting from its phase‐transition capacity. This investigation offers a facile and versatile way to construct an ideal gel electrolyte for next‐generation energy storage devices. Abstract : A crystal‐type composite gel electrolyte is prepared by the hydrated crystallization of NaAc within a hydrogel. The electrolyte possesses excellent comprehensive performance, including ultrahigh toughness, high electrochemical stability window, and extreme temperature tolerance. More significantly, a supercapacitor employed with this electrolyte can work in fire or in liquid nitrogen within a short amount of time owing to the phase transition of the electrolyte.